Penerapan model pembelajaran cooperative integrated reading and composition untuk meningkatkan keterampilan membaca pemahaman peserta didik kelas iv sekolah dasar - Dewi Endrasti (Universitas Sebelas Maret, 2019)
Abstract. The aim of this research was to improve reading comprehension skill by applied CIRC at fourth grade students of SDN Ngoto at the academic year 2018/2019.This classroom action research is held in two cycles. Each cycles consisted of planning, action, observation, and reflection. Data collection techniques were observation, interview, test and document study. Quantitative data analysis techniques in this research implemented a comparative descriptive technique, and qualitative data analysis techniques implemented a critical analysis technique.The data validity was investigated by content validity and triangulation methods. The improvement can be known from increased number of students who categorized as skilled in reading comprehension in each cycle. The percentage of classical completeness in the pre-action was only 14,29% increased to 40,74% in cycle I and increased to 84,62% in cycle II. The conclusion of this research is the implementation of CIRC model can increase reading comprehension skill at the fourth grade students of SDN Ngoto at the academic year 2018/2019. Keywords: Cooperative Integrated Reading and Composition, Reading Comprehension Skill, Elementary School.